Implementasi Sistem Informasi Dayah Dan Pemetaan Lokasi Berbasis Sistem Informasi Geografis - Ula, Mutammimul; Fajri, Riyadhul; Cinni Ujung, Yella (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
The application of information technology is one of the advantages of processing Islamic boarding school information systems. It significantly impacts making Islamic boarding school information along with the intended Islamic boarding school location and location. The problem that occurs is that many systems in institutions or agencies initially collect data manually in detail about the profile of the Islamic boarding school and its location, making it an obstacle for the community in determining the choice of an Islamic boarding school. The aim is to make it easier to manage data and prepare a Geographic Information System for data. The research objective is to make it easier for the dayah to collect data and make it easier for the community to process Geographic Information Systems for the dayah. This research was developed on a GIS basis and in location processing by converting the files into Geo JSON and Leaflet JS formats to visualize the mapping of the intended dayah locations. Testing the system application menu is done with the black box testing model. The results of this study can facilitate the dayah in managing the power information system and the accuracy in knowing the location of the dayah information. The results of testing the dayah application menu following the results of 100% according to the test results on a running web application by displaying 100% results with the appearance of the appropriate information system application and mapper